Renewal of the public sector in Nepal for good governance - Rajbhandary, Achyut Bahadur (1998)
The Nepalese public sector is based on the old model where power is centralized at the political level and the governance is rendered impersonally through subordinated officials. There has been no change in it even after the advent of the multi-party democracy. The author explains how a yawning gap has come to exist between the old-fashioned public sector management in Nepal, the new Constitution, the ideal of the liberal society and the changed global environment. With so much of anachronism to correct and with so much novelty of good governance to aim ahead, the author alarmingly terms the task as the `renewal' of the public sector system. As a prelude to his renewal agenda, the author makes a number of comments on the HMG Transanction of Business Rules (TBR) which has long forced the Government to live and work within the trammels of a closed system despite its pledges to obtain `wider participation of the people'. He points out the scanty and archaic institutional arrangements in the TBR purported to support the Cabinet through its Constitutional role and liabilities. He considers that a complete overhaul of the TBR, a discontinuity with the past hangover and the Parliament's legislative initiative in designing an innovative public sector management would make a starting point for construction of good governance in Nepal. The author then identifies five cardinal factors that might usher an environment of good governance in the Nepalese context, and discusses their possible approaches in the existing situation. - Reproduced
Keywords: Public administration - Nepal; Public sector - Nepal; Public sector